DIMENSIONS OF HISTORICAL MEMORY: SOCIAL FABRIC,ASSOCIATIVITY, ETHICS-POLITICS - Prada Galvis, Alberto (2022)
The peace agreement signed by the Colombian government and FARC- EP, recognizes the victims of violence, as the main actor in the armed conflict. In order to complay with objective number 5 of the accord, a whole new system which aims at every victim´s right to expect truth, justice, reparation and guarantee of not repetition, has been created. The peace agreement also takes into account the repositioning of survivors´s historical memory.Accordingly, the current Project analyses, throughtout a systematic revision how important historical memory is for rebuilding the social fabric, helping the associativity as an initiative, and also contemplates the ethical– political perspective as a key element. A qualitative research method has been carried out by implementing an electronic search on different sources of information, based on English and Spanish articles, published from2010 until 2019 on databases such Science Direct, Scopus, SPRINGER, Taylor & Francis, OXFORD, PSICODOC, EBSCOHOST, PSYCARTICLES, Jstor, PubMed, ERIC, Medline, Redalyc and Scielo. All of them focused on the studies categories in Colombia, with some characteristics of PRISMA. Theresults give account of the need of transforming the emphasis that historical memory has, into something that develops practices and strategies of empowerment and dignity. It is necessary to keep on working on historical memory research projects, as to resignify victims as subjects of rights